2014
DOI: 10.1155/2014/723280
|View full text |Cite
|
Sign up to set email alerts
|

Work-Related Health Disorders among Saudi Computer Users

Abstract: The present study was conducted to investigate the prevalence of musculoskeletal disorders and eye and vision complaints among the computer users of King Abdulaziz University (KAU), Saudi Arabian Airlines (SAUDIA), and Saudi Telecom Company (STC). Stratified random samples of the work stations and operators at each of the studied institutions were selected and the ergonomics of the work stations were assessed and the operators' health complaints were investigated. The average ergonomic score of the studied wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 51 publications
(15 reference statements)
3
23
0
Order By: Relevance
“…The present findings are in agreement with related empirical findings. For example, the present finding on non-provision of ergonomics comfortable computer workstation is in consonance with the findings of Asaolu and Itsekor (2014), (Momodu Bayo et al, 2014), (Jomoah, 2014) who found that the incidences of general complaints of computer users surround the poor or decrease in work station ergonomics provisions. In Nigeria, this can be in connection with recent findings by Olabode et al (2017) that several factors such as awareness, resources constraints, communication and integration disconnection between employees and equipment designers, technological changes and insufficient relevant studies inhibited the efficient implementations in Nigeria.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The present findings are in agreement with related empirical findings. For example, the present finding on non-provision of ergonomics comfortable computer workstation is in consonance with the findings of Asaolu and Itsekor (2014), (Momodu Bayo et al, 2014), (Jomoah, 2014) who found that the incidences of general complaints of computer users surround the poor or decrease in work station ergonomics provisions. In Nigeria, this can be in connection with recent findings by Olabode et al (2017) that several factors such as awareness, resources constraints, communication and integration disconnection between employees and equipment designers, technological changes and insufficient relevant studies inhibited the efficient implementations in Nigeria.…”
Section: Discussionsupporting
confidence: 92%
“…For instance , Johnson, Onigbinde, Onasanya, Emechete, and Gbela (2009) observed in Nigeria University community, that common complaint among computer users is back pain, neck, eyes and wrist pain. Also, Jomoah (2014) found that computer users' complaints increase with the decrease in workstation ergonomic score, progress of age and duration of employment. Past empirical findings have reported the effect of age on technostress.…”
Section: Introductionmentioning
confidence: 97%
“…Neglecting the principles of ergonomics during computer utility raises the risk of health problems [5]. Musculoskeletal disorders (MSDs), Visual symptoms and Insomnia are the common health problems amongst computer users [6][7][8][9]. ''Musculoskeletal disorders'' covers an extensive range of conditions affecting the musculoskeletal system including the joints, muscles, tendons, ligaments, peripheral nerves, and supporting blood vessels [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…[2] It is reported that 25% of computer users are suffering from CRIs and MSDs are the most prevalent disorders among office workers. [3,4] The neck and shoulders pain was mostly experienced by the office workers, followed by CVS such as eyestrain, blurred vision, and headache. [4,5] It is undeniable that computer is an important device to manage a lot of activities and jobs, but a long period of using a computer may increase the chances of developing CRIs.…”
Section: Introductionmentioning
confidence: 99%